A Comparative Study of ULF Waves' Role in the Dynamics of Charged Particles in the Plasmasphere: Van Allen Probes Observation. Issue 7 (5th July 2018) - Ren, Jie; Zong, Q. G.; Miyoshi, Y.; Rankin, R.; Spence, H. E.; Funsten, H. O.; Wygant, J. R.; Kletzing, C. A.
Abstract: By analyzing observations from Van Allen Probes in its inbound and outbound orbits, we present evidence of coherent enhancement of cold plasmaspheric electrons and ions due to drift‐bounce resonance with ultralow frequency (ULF) waves. From 18:00 UT on 28 May 2017 to 10:00 UT on 29 May 2017, newly formed poloidal mode standing ULF waves with significant electric field oscillations were observed in two consecutive orbits when Probe B was traveling inbound. In contrast to observations during outbound orbits, the cold (<150 eV) electrons measured by the HOPE instrument were characterized by flux enhancements several times larger and bidirectional pitch angle distributions during inbound orbits. The electron number density inferred from upper hybrid waves is twice as larger as during inbound orbits, which were also confirmed by an increase of spacecraft potential. The observed ULF waves are identified as second harmonic modes that satisfy the drift‐bounce resonant condition of N = 1 with cold electrons. An enhancement of the plasmaspheric ion number density to restore charge neutrality of plasmas in inbound orbits is observed, which is associated with an increase of ULF wave periods. The observations suggest that the dynamics of plasmaspheric electrons is modified by ULF waves through drift‐bounce resonance and that plasmaspheric ions are indirectly impacted. Key Points: Cold plasmaspheric electron and ion enhancement by ULF waves are reported using spacecraft observations Cold electrons are accelerated by ULF waves through drift‐bounce resonance, and cold ions are enhanced to restore the charge neutrality This study reveals the role of ULF waves in affecting the dynamics of plasmapshere